2022
DOI: 10.3389/fendo.2022.703733
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 Mediates Proliferation, Migration, and Invasion Promoted by Estradiol in Human Glioblastoma Cells

Abstract: Glioblastomas (GBM) are the most frequent and aggressive brain tumors. 17β-estradiol (E2) increases proliferation, migration, and invasion of human GBM cells; however underlying mechanisms are no fully understood. Zeste 2 Enhancer Homologous enzyme (EZH2) is a methyltransferase part of Polycomb 2 repressor complex (PRC2). In GBM, EZH2 is overexpressed and involved in the cell cycle, migration, and invasion processes. We studied the role of EZH2 in the pro-oncogenic actions of E2 in human GBM cells. EZH2 gene s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…EZH2 is a S-adenosyl-L-methionine (SAM)-dependent methyltransferase, and its role as an epigenetic modulator in different types of cancer has been widely investigated. In GBM, EZH2 overexpression has been correlated with poor prognosis [ 57 , 58 ]. Although little is known about the mechanistic aspects of EZH2 activity in GBM, the inhibition of EZH2 expression by miR-340 in triple negative breast cancer has led to decreased levels of miR-21, revealing a key miRNA network pathway [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…EZH2 is a S-adenosyl-L-methionine (SAM)-dependent methyltransferase, and its role as an epigenetic modulator in different types of cancer has been widely investigated. In GBM, EZH2 overexpression has been correlated with poor prognosis [ 57 , 58 ]. Although little is known about the mechanistic aspects of EZH2 activity in GBM, the inhibition of EZH2 expression by miR-340 in triple negative breast cancer has led to decreased levels of miR-21, revealing a key miRNA network pathway [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Methyl 3′-(2,4-Bis(benzyloxy)-5-isopropyl-N-methylbenzamido)-5-(ethyl(tetrahydro-2H-pyran-4-yl)amino)-4-methyl-[1,1′-biphenyl]-3-carboxylate (30). Intermediate 30 was synthesized in 70% yield from starting material 21 like that described for the synthesis of compound 26.…”
Section: Methyl′-(n-benzyl-24-bis(benzyloxy)-5-isopropylbenzamido)-5-...mentioning
confidence: 99%
“…An extensive literature survey led us to arrive at the emerging candidature of EZH2 as an epigenetic target for GBM. EZH2, a crux subunit of the Polycomb Repressive Complex (PRC2), is responsible for methylating lysine 27 (mono-, di-, and trimethylation) in histone H3 (H3K27) and H3K27me3 is more frequently interlinked with transcriptional repression. Notably, EZH2 is overexpressed in cancer stem cells of malignant tumors and plays a critical role in cancer stem cell expansion and maintenance. Several key revelations ascertain the involvement of EZH2 in GBM initiation and progression, such as (i) involvement of miR-206/Twist axis in EZH2-regulated malignancy of GBM cells, (ii) pro-oncogenic actions of Estradiol (proliferation, migration, and invasion) by EZH2 in GBM cells, and (iii) direct transcriptional regulation of c-myc by EZH2 leading to the maintenance of GSCs . To validate EZH2 as a therapeutic target in GBM and capitalize on the aforementioned revelations, several EZH2 inhibitors (Figure ) were evaluated (monotherapy/combination therapy) and optimistic results were attained, for instance, (i) GSK343, a highly potent and selective EZH2 inhibitor, demonstrated the ability to counteract GBM progression via modulation of canonical/noncanonical NF -κB/IκBα pathways and immune response; (ii) a cocktail of tazemetostat (EZH2 inhibitor) and PI-103 (PI3K inhibitor) exerted significant reduction in GBM progression (U-87 cells); (iii) HOTAIR-EZH2 inhibitor AC1Q3QWB in combination with GSK-LSD1 inhibitor elicited enhanced antitumor efficacy in GBM patient-derived xenograft (PDX) models; (iv) combination of HOTAIR-EZH2 inhibitor (AQB) and palbociclib inhibitors suppressed the cell cycle in gliomas with high expression of EZH2 and low expression of CWF19L1; and (v) treatment with EZH2 inhibitors MC4040 and MC4041 led to impairment of primary GBM cell viability and weakened the aggressive malignant phenotype by reducing angiogenesis …”
Section: Introductionmentioning
confidence: 99%
“…To elucidate how PRMT6 enhances the invasion of GBM cells, we rst analyzed the previously completed proteomic data [19] and found that the protein level of EZH2 was signi cantly down-regulated in PRMT6de cient U87 cells. EZH2 has been con rmed to be a key regulator of enhanced glioma cell invasiveness [24]. Therefore, to explore whether PRMT6 has a regulatory effect on EZH2 in GBM cells, we examined the in uence of PRMT6 silencing or overexpression on EZH2 expression.…”
Section: Prmt6 Enhances the Protein Stability Of Ezh2 By Attenuating ...mentioning
confidence: 99%
“…EZH2 serves as a crucial intermediary regulatory factor that enhances proliferation, migration, and invasion of glioma cells [24]. Studies have demonstrated that reducing EZH2 levels can decrease the invasive, migratory, and proliferative abilities of glioma cells, while also promoting apoptotic processes [25].…”
mentioning
confidence: 99%